Islamic Communication Strategies in Addressing Religious Hoaxes on Social Media - Hasmuni Hasmuni; Marhamah Marhamah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The development of digital media has changed the way Indonesians access and disseminate religious information, creating vulnerability to hoaxes that impact behavior, perceptions, and the dynamics of religious diversity in both public and private spaces. This study aims to understand how religious hoaxes are constructed and disseminated on social media, as well as how emotions, identity, and digital authority shape user responses. Using a qualitative approach with a case study design based on document analysis, this study examines news archives, fact-checking databases, national hoax monitoring reports, and digital traces from various social media platforms. Thematic analysis was used to identify patterns of meaning that emerged in circulating religious narratives. The results reveal four main findings: the use of religious arguments and aesthetics in building narrative authority; the exploitation of fear, guilt, and chain logic; the shift of religious authority towards algorithm-based legitimacy and virality; and the normalization of hoax dissemination in private spaces reinforced by a culture of digital charity. These findings enrich the study of Islamic communication, media ecology, and disinformation studies by emphasizing that hoax mitigation requires an ethical-spiritual approach that can address the affective and identity dimensions of users. In practical terms, this research provides direction for strengthening religious digital literacy and public communication strategies that are more adaptive to the algorithmic dynamics and digital culture of society.